Dynamics of Mutations and Promotion of Structural Positions of Civil Servants in Malaka Regency - Melkisedek. N.B.C. NEOLAKA; Ajis Salim Adang DJAHA; Alfred Omri Ena MAU; David Wilfrid RIHI (Indonesia Strategic Sustainability, 2023)
The purpose of effective transfers and promotions leads to increasing the effectiveness of local government organizations, but the good intentions of the regional leadership of Malacca Regency, in this case the Regent as PPK, to manage the performance of civil servants within the Malacca Regency Government, received criticism from several parties who stated that the transfer carried out violated procedures. not in accordance with the terms and conditions of KKN. This research is a qualitative research with primary and secondary data types collected through interviews, documentation and observation and then the data that has been collected is analyzed using data analysis techniques from Miles & Huberman (1992:16) consisting of three streams of activities that occur simultaneously, namely : data reduction, data presentation, conclusion/verification. Study's result found that the dynamics of mutation and promotion of structural positions of civil servants in Malacca Regency in terms of mutations were not effective because they were carried out as a form of sanction as a result of not supporting the elected Regent and Deputy Regent to win the 2020 Malacca Regional Election while promotions for PNS positions were carried out because there was a mechanism remuneration because the civil servants who will be promoted are the success team to win the elected regent in the 2020 Malacca regional elections, while the inhibiting factors for the effectiveness of the transfer and promotion of structural positions of civil servants in Malacca Regency are due to the patron client relationship and the promise of position compensation.